2019
DOI: 10.5539/gjhs.v11n9p102
|View full text |Cite
|
Sign up to set email alerts
|

Difficult Laparoscopic Cholecystectomy

Abstract: Laparoscopic cholecystectomy is as much easy procedure as difficult one. Surgeon should consider every case as his first one. Intraoperative complications are common while transformation to open surgery should be always in consideration. Transformation to open cholecystectomy isn't a sign of lack of experience, rather it is a proof of surgeon cleverness and an evidence of professional competence as it could keep our patient away from life-threatening complications in difficult situations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
2
1
1
Order By: Relevance
“…In the current study found female preponderance (88.1%), a finding which is in consistence with several study reports [2,6,12,15,21,22,23,27,28]. High incidence of gallstones in females has been suggested due to the effect of estrogen and progesterone on biliary cholesterol level and gallbladder motility [2,6].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the current study found female preponderance (88.1%), a finding which is in consistence with several study reports [2,6,12,15,21,22,23,27,28]. High incidence of gallstones in females has been suggested due to the effect of estrogen and progesterone on biliary cholesterol level and gallbladder motility [2,6].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, difficult laparoscopic cholecystectomy confronted the surgical team in 137 patients (33.8%), which is similar to what were reported by Atta H et al (32%) [7], Mudgal M (34%) [15], as well as Singh K et al (34%) [22], and located between the two extreme ratios which were mentioned by Nidoni R et al (24.4%) [17],and Verma D et al (46%) [29]. The study showed conversion rate of 6.4%, which compares well with the incidence reported in the literature, which varies from 2-15% [6,17,21,22,23].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations